ANALISIS FRAUD DIAMOND DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN (Studi pada Perusahaan Property, Real Estate, and Building Construction yang terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Oktavianto Kurniawan, 17.05.62.0014; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of diamond fraud on fraudulent financial statements. This study uses a sample of property, real estate and building construction companies listed on the Indonesia Stock Exchange (IDX) for the period 2015 to 2017. The number of companies sampled is 30 companies with. purposive sampling method, the total sample obtained was 90. The method of data analysis in this study used the logistic regression analysis method. The results of this study indicate that Nature of Industry has an effect on financial statement fraud. While Financial Target, External Pressure, Rationalization, and Capability do not affect the financial statement fraud.